Effects of maternal age and stress on offspring quality in a viviparous fly - Lord, J; Leyland, R; Haines, L; Barreaux, A; Bonsall, M; Torr, S; English, S (Wiley, 2021)
Many organisms show signs of deterioration with age in terms of survival and reproduction. We tested whether intraspecific variation in such senescence patterns can be driven by resource availability or reproductive history. We did this by manipulating nutritional stress and age at first reproduction and measuring age-dependent reproductive output in tsetse (Glossina morsitans morsitans), a viviparous fly with high maternal allocation. Across all treatments, offspring weight followed a bell-shaped curve with maternal age. Nutritionally stressed females had a higher probability of abortion and produced offspring with lower starvation tolerance. There was no evidence of an increased rate of reproductive senescence in nutritionally stressed females, or a reduced rate due to delayed mating, as measured by patterns of abortion, offspring weight or offspring starvation tolerance. Therefore, although we found evidence of reproductive senescence in tsetse, our results did not indicate that resource allocation trade-offs or costs of reproduction increase the rate of senescence.